2017
DOI: 10.1515/jos-2017-0044
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Classification Errors Under Edit Restrictions in Composite Survey-Register Data Using Multiple Imputation Latent Class Modelling (MILC)

Abstract: Both registers and surveys can contain classification errors. These errors can be estimated by making use of a composite data set. We propose a new method based on latent class modelling to estimate the number of classification errors across several sources while taking into account impossible combinations with scores on other variables. Furthermore, the latent class model, by multiply imputing a new variable, enhances the quality of statistics based on the composite data set. The performance of this method is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…This is in practice also not often the case, although this is commonly assumed by many researchers. Recently, imputation methods have been developed to take misclassification in combined data sets into account, for example by assuming that a certain proportion of the data is misclassified (Manrique-Vallier and Reiter 2016) or by estimating the number of misclassified units by using information from multiple sources (Boeschoten et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This is in practice also not often the case, although this is commonly assumed by many researchers. Recently, imputation methods have been developed to take misclassification in combined data sets into account, for example by assuming that a certain proportion of the data is misclassified (Manrique-Vallier and Reiter 2016) or by estimating the number of misclassified units by using information from multiple sources (Boeschoten et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Boeschoten et al . () also use an LC model to model the true value of a variable that is observed (with measurement error) in multiple sources. We sketch their approach.…”
Section: Basic Situations and Their Methodsmentioning
confidence: 99%
“…The method proposed by Boeschoten et al . () starts with the original combined data set and then proceeds with five steps. Select m bootstrap samples from the original combined data set. Create an LC model for every bootstrap sample. Multiply impute latent ‘true' variable X for each bootstrap sample.…”
Section: Basic Situations and Their Methodsmentioning
confidence: 99%
“…Boeschoten et al . () showed that the performance of the MILC method is closely related to the entropy R 2 of the corresponding latent class model.…”
Section: Applying the Extended Multiple Imputation Of Latent Classes mentioning
confidence: 99%
“…Boeschoten et al . () introduced the MILC method and evaluated the method under a range of conditions in terms of data quality. In addition, Boeschoten et al .…”
Section: Applying the Extended Multiple Imputation Of Latent Classes mentioning
confidence: 99%